In vitro drug sensitivity predicts response and survival after individualized sensitivity-directed chemotherapy in metastatic melanoma: a multicenter phase II trial of the Dermatologic Cooperative Oncology Group - Ugurel, Selma; Schadendorf, Dirk; Figl, Adina; Rittgen, Werner; Delorme, Stefan (Clinical cancer research, 2006)
Purpose:In vitro sensitivity assays are promising tools to predict the individual outcome of different chemotherapy regimens. However, a direct association between in vitro and in vivo chemosensitivity has to be shown by clinical studies. This multicenter phase II trial was aimed to investigate the efficacy of a sensitivity-directed, first-line chemotherapy in metastasized melanoma patients, and to prove an association between in vitro sensitivity and therapy outcome. - Patients and Methods: The primary study end point was objective response; secondary end points were safety, overall survival, and progression-free survival. Viable tumor cells obtained from metastatic lesions were tested for chemosensitivity to seven single drugs and five drug combinations using an ATP-based luminescence viability assay. - Results: Out of 82 recruited patients (intention-to-treat), 57 received assay-directed chemotherapy and 53 were evaluable for all study end points (per protocol). The drug combinations used were gemcitabine + treosulfan, paclitaxel + cisplatin, paclitaxel + doxorubicin, and gemcitabine + cisplatin. The per protocol population could be divided into 22 (42%) chemosensitive and 31 (58%) chemoresistant patients by an arbitrary chemosensitivity index. Objective response was 36.4% in chemosensitive patients compared with 16.1% in chemoresistant patients (P = 0.114); progression arrest (complete response + partial response + stable disease) was 59.1% versus 22.6% (P = 0.01). Chemosensitive patients showed an increased overall survival of 14.6 months compared with 7.4 months in chemoresistant patients (P = 0.041). - Conclusion:In vitro chemosensitivity testing may be worthy of further exploration to see if it could be a useful tool to predict the outcome of melanoma patients treated with a sensitivity-directed chemotherapy. Therefore, these preliminary results will be evaluated by a planned phase III trial using a randomized, standard-regimen controlled setting.
Gesehen am 05.02.2021